Pengaruh Employee Engagement dan Employee Value Proposition terhadap Kinerja - Sumarni, Murti (Universitas PGRI Yogyakarta, 2016)
The aim of this research was focused to determine the impact of Employee Engagement and Employee Value Proposition to Performance. The reliability and validity test was conducted to 30 respondents and the result showed that all questions item were proven valid and reliable to be used in further research analysis. Populations in this research were the employees of PT. Bank Mega, Tbk. Branch Office Semarang. Questionnaire wasused to collect the data in the amount of 50 respondents. This research used SPSS to analyze and the result of the regression analysis indicated that the Employee Engagement and Employee Value Proposition had a significant effect to Performance. The result of Path Analysis indicated that Employee Value Proposition could be a moderating variable between the impact of Employee Engagement to Performance.